OLIGODYNAMIC EFFECT OF PRECIOUS METALS ON SKIN BACTERIA (FUDMA JOURNAL OF SCIENCES, 2020)
The oligodynamic hold of gold and silver is extant and extremely relevant as a proactive measure against infections. The antimicrobial effect of gold and silver jewelries was determined on skin bacteria by introducing them into culture plates already inoculated with bacterial isolates; Staphylococcus aureus, Staphylococcus epidermidis and Pseudomonas aeruginosa from the wrist, neck and ear regions of the skin. Samples were collected by swab sampling and isolates were identified by their cultural morphology and biochemical characterization. Results showed that both precious metals were able to inhibit all three bacteria with silver jewelries giving wider zones of inhibition measuring between 3 mm to 7 mm while gold jewelries gave zones of inhibition between 1 mm to 4 mm. The culture plates containing Pseudomonas aeruginosa recorded the highest zone of inhibition while the least was observed in the culture plates that contained Staphylococcus epidermidis. No zone of inhibition was observed with ordinary golden-coloured and silver-coloured jewelries which served as negative control. This study showed that gold and silver are oligodynamic with silver having a higher oligodynamic efficacy on the skin bacteria tested Key Words:Precious metals, Oligodynamic efficacy, Skin bacteria
Keywords: Precious metals, Oligodynamic efficacy, Skin bacteria